PENGARUH KOMPENSASI TERHADAP TURNOVER INTENTION YANG DIMEDIASI OLEH ORGANIZATIONAL COMMITMENT KARYAWAN PT IDX - Fransiskus Billy Sandy (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2019)
This study aims to determine the condition of the Compensation, Organizational Commitment, and Turnover Intention on employees of PT IDX. The population in this study were employees of PT IDX totaling 108 employees. Data retrieval is done by using questionnaire. Data is processed using SPSS ver. 25 for Window and Hayes Macro Process. The results of the study show that: First, the Compensation has no significant effect on Turnover Intention. Second, the Compensation has a positive and significant effect on the Organizational Commitment. Third, the Organization Commitment has a negative and significant effect on Turnover Intention. Fourth, the Organizational Commitment mediates the relationship between the Compensation to Turnover Intention.